Experimental and numerical study of dynamic performance of CVAR subjected to regular wave and platform motion. (1st March 2020) - Lou, Min; Liang, Weixing; Li, Run
Abstract: Compliant vertical access risers (CVAR) offer significant economic benefits and prospects for development because of their special configuration. In this paper, the dynamic performance of CVAR is studied by model experiments and numerical simulations. Based on virtual work and variational principles, a vibration equation considering the large deformation mechanical behaviors of CVAR with the influences of bending stiffness and non-uniform internal flow is proposed. To verify it, model experiments on the CVAR are firstly conducted and compared the results with those of a numerical simulation. Time-domain analyses of key nodes, regular wave analysis and dynamic response at different positions of the buoyancy module were then carried out. The vibration near the platform was the largest due to the wave load, and decreased rapidly when in the transitional region. The minimum tension of the transition zone was even subzero at the far end, which means the CVAR is unstable when the platform subject to regular wave conditions. When the buoyancy block was above 1000 m, tension at the bottom was smaller than 672 kN, which will cause the lower region to become catenary shaped and the CVAR to lose its unique operational advantage. Highlights: The dynamic performance of CVAR subjected to regular wave and platform motion is analyzed by experiments and simulations. The model considers the large deformation of CVAR with the influences of bending stiffness and non-uniform internal flow. We firstly conducted model experiments on the CVAR and compared the results with those of a numerical simulation.